Kreatifitas Ilmiah melalui Pelatihan Skripsi Berbasis SPSS - Efa Irdhayanti; Rizani Ramadhan; Anggraini Syahputri; Mazayatul Mufrihah (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
In today's digital era, mastery of technology and data analysis software is a skill that is very much needed by students, especially those involved in research and data analysis. SPPSS (Statistical Package For The Social Sciences) is one of the software that is widely used for statistical analysis in various disciplines, including social sciences, health, economics and education. The problems faced by final semester students in processing research data where the processing of funds is still done manually or still using Microsoft Excel software. In overcoming these problems, the PKM team provides solutions through Data Processing Training Using SPSS Software to improve scientific creativity in students. The output target in this PKM activity is that final semester students, namely semesters 6 and 8 in Pontianak City are able to use data processing media using SPSS (Statistical Package For The Social Sciences). Specifically, the output targets of PKM activities are: (1). Students are able to use data according to the research design that has been determined and is right, (2). Students are able to process research data quickly and precisely according to the existing research design. In the implementation of this PKM program has been carried out well and smoothly as planned. Participants were able to receive the material delivered by the PKM Team well and participants were very enthusiastic about participating in this training activity which can be seen through the activeness of participants in the activity process.